Application of the Sequential Control for Increasing Competitiveness of Agricultural Products - Puzik, Vladimir; Puzik, Ludmila; Lyubymova, Nina; Pankova, Oksana; Sakhatsky, Vitalyi (International Journal of Engineering and Technology, 2018)
The competitiveness of agricultural enterprises on the international market depends directly on the professional and timely implementation of decisions of control. Its function stipulates for a number of actions, work out methods and tools which aimed at conservation the quality of agricultural products in the period of its storage and transportation in accordance with the consumerâ€™s requirements.Construction of control by a recycling pattern is one of the practical ways to increase the effectiveness of control, when an object that is recognized as fit is subject to repeated checks. The major tasks in the construction of a statistical model of measurement control have been analyzed, a typical monitoring system, a sequential control structure, and its characteristics have been submitted. The suggested control significantly reduces the reject rate in the total mass of products.The obtained result of analytical dependencies is convenient for engineering calculations of other types of numerical control.An example of the application of sequential control of broccoli cabbage in its storage with helping with antiseptic preparations is given. The influence of various antiseptics on different varieties of broccoli cabbage is considered. Such a study helps the manufacturer find the best opportunities to improve the competitiveness of its products.Â Â
Keywords: Agriculture; Antiseptic; Broccoli; Competitiveness; Management quality; Practice; Products; Sequential control.